1999
DOI: 10.1016/s1097-2765(00)80358-5
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Mechanism for the Phosphorylation-Dependent Regulation of Heterotrimeric G Proteins by Phosducin

Abstract: Visual signal transduction is a nearly noise-free process that is exquisitely well regulated over a wide dynamic range of light intensity. A key component in dark/light adaptation is phosducin, a phosphorylatable protein that modulates the amount of transducin heterotrimer (Gt alpha beta gamma) available through sequestration of the beta gamma subunits (Gt beta gamma). The structure of the phosphophosducin/Gt beta gamma complex combined with mutational and biophysical analysis provides a stereochemical mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 31 publications
4
74
0
Order By: Relevance
“…These observations were consistent with the finding that Pdc formed a soluble complex with G t βγ by blocking its binding to rod disc membranes [14]. Third, phosphorylation of Pdc at the major PKA site (serine 73 (S73) in most mammals, serine 71 in the mouse) resulted in destabilization of helix 2 of Pdc, which uncovered residues of G t βγ involved in the G t α interaction that might allow G t α to displace Pdc from G t βγ [40]. This later finding provided a possible mechanism by which Pdc phosphorylation could regulate the interaction between G t βγ and G t α.…”
Section: Early Observations -The Gβγ Sequestration Hypothesissupporting
confidence: 84%
See 1 more Smart Citation
“…These observations were consistent with the finding that Pdc formed a soluble complex with G t βγ by blocking its binding to rod disc membranes [14]. Third, phosphorylation of Pdc at the major PKA site (serine 73 (S73) in most mammals, serine 71 in the mouse) resulted in destabilization of helix 2 of Pdc, which uncovered residues of G t βγ involved in the G t α interaction that might allow G t α to displace Pdc from G t βγ [40]. This later finding provided a possible mechanism by which Pdc phosphorylation could regulate the interaction between G t βγ and G t α.…”
Section: Early Observations -The Gβγ Sequestration Hypothesissupporting
confidence: 84%
“…However, careful measurements of Pdc binding to G t βγ showed that PKA phosphorylation only decreased the binding by 3-fold [47,48]. In fact, the complex between PKA phosphorylated Pdc and G t βγ was crystallized and its structure determined as mentioned above [40]. These findings raised questions about whether Pdc and G t βγ actually dissociated upon PKA phosphorylation in the dark.…”
Section: Modifying the Model -New Clues About Pdc Functionmentioning
confidence: 99%
“…Upon exposure to light, phosducin is dephosphorylated by PP2A (19, 21). The dephosphorylated species of phosducin, no longer binding 14-3-3 protein, is more efficient in sequestering the γ subunits of transducin (65). Therefore, dephosphorylation of phosducin by PP2A establishes the conditions for phosducin to modulate the amplification of cGMP hydrolysis by preventing the recycling of transducin with the activated rhodopsin.…”
Section: Discussionmentioning
confidence: 99%
“…These effects have been studied extensively in vitro (16,18,20,21,34), but have not been examined in vivo. To address this issue, the binding of Pdc to G t ␤␥ was measured in light-or dark-adapted retina and was compared with the phosphorylation of Ser-54 and Ser-73.…”
Section: Stoichiometry Of Ser-54 and Ser-73 Phosphorylation-ifmentioning
confidence: 99%